Inovasi Teknologi Untuk Industrialisasi Pedesaan Serta Implikasinya Bagi Kinerja Ekonomi Industri Kecil Agro - Charina, Anne; Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The notion of rural industrialization and how it can enhance the economic growth of small industries is still an issue that needs attention especially by policy makers. This study seeks to build understanding, knowledge and awareness on how leveraging technological innovations will help build strong rural industrialization and bring positive changes especially to the economic performance of small industries in rural areas. In this study, questionnaires were distributed to 127 participants consisting of small agro-industry entrepreneurs in Tasikmalaya district, a pilot project area for small agro-industry development in West Java. SPSS version (24.0) was used for data analysis. The findings of this study show that 58% of small agro-industry entrepreneurs have successfully adopted better technology than the generation before them, which has had positive implications for increasing their business profitability over the past three years. Policies designed can focus on improving the quality of corporate capital (economic capital, social capital and human capital) which is expected to be able to bridge the problems faced by small agro-industries in rural areas.